Analisis Pengaruh Waktu Pemanasan Terhadap Kadar Oksalat Dalam Bayam Hijau (Amarantus hybridus) Dengan Menggunakan Metode Spektrofotometri UV-Vis - Rusvirman Muchtar; Yusi Fudiesta; Sukrido Sukrido; Devi Windaryanti (Jurnal Sains dan Kesehatan, 2017)
Green spinach( Amaranthus hybridus) was utilized as complement of food as vegetable as spinach is cooked through instillation process with stewed (clear spinach vegetable) and slicing (spinach vegetable). Besides contains a lot of nutrient, spinach also contain substance anti nutrient which is oxalate what do get to precipate calcium and forms calcium oxalate that can't be absorbed by body, so formed by causative dissolvable salt sediment its appearance calculus disease. After been done research to spinach vegetable of trick second upon with at poaching was gotten by content oxalate as big as 0,108 g (without condiment) and 0,112 g (with condiment) with optimum time 3 minutes. On brew with slicing oxalate content 0,112 g (without condiment) and 0,125 g (with condiment) with maximum time 5 minutes. Measurement oxalate content utilizes UV Vis's Spectrophotometer method on wavelength 345 nm. Oxalat's rate in green spinach lies under letal dose is contemned according to BADAN POM RI 2012 (6 - 8 g).